Semiconductor basics : a qualitative, non-mathematical explanation of how semiconductors work and how they are used - Domingo, George, 1937- (Wiley, 2020)
"An accessible guide to how semiconductor electronics work and how they are manufactured, for professionals and interested readers with no electronics engineering background Semiconductor Basics is an accessible guide to how semiconductors work. It is written for readers without an electronic engineering background. Semiconductors are the basis for almost all modern electronic devices. The author, an expert on the topic, explores the fundamental concepts of what a semiconductor is, the different types in use, and how they are different from conductors and insulators. The book has a large number of helpful and illustrative drawings, photos, and figures. The author uses only simple arithmetic to help understand the device operation and applications. The book reviews the key devices that can be constructed using semiconductor materials such as diodes and transistors and all the large electronic systems based on these two component such as computers, memories, LCDs and related technology like Lasers LEDs and infrared detectors. The text also explores integrated circuits and explains how they are fabricated. The author concludes with some projections about what can be expected in the future"--